2020
DOI: 10.1111/dme.14354
|View full text |Cite
|
Sign up to set email alerts
|

The psychosocial experience and needs of children newly diagnosed with type 1 diabetes from their own perspective: a systematic and narrative review

Abstract: Aim To understand the psychosocial experience of children and identify their primary support needs following a type 1 diabetes diagnosis. Methods A systematic review and narrative synthesis of the literature in this area was conducted. Results A total of 32 studies were included in the review. At diagnosis, the majority of children experienced high distress, including grief, anxiety, anger, irritation and injection anxiety. The intensity of this reaction decreased rapidly over the following weeks. At diagnosis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 46 publications
(233 reference statements)
0
21
0
Order By: Relevance
“…As young children's views and competencies in relation to diabetes care are largely missing from the literature (4,13,19), it is difficult to compare our result with findings from other studies. However, our findings suggest that young children, like older children and adults, have a need for and benefit greatly from CCC practices.…”
Section: Discussionmentioning
confidence: 69%
“…As young children's views and competencies in relation to diabetes care are largely missing from the literature (4,13,19), it is difficult to compare our result with findings from other studies. However, our findings suggest that young children, like older children and adults, have a need for and benefit greatly from CCC practices.…”
Section: Discussionmentioning
confidence: 69%
“…16 A growing body of literature has demonstrated that improving patients’ psychosocial adaptation was an effective strategy to alleviate psychological distress and improve patients’ quality of life in various chronic care contexts (e.g., diabetes and kidney disease). 17 , 18 Despite an increasing incidence of IBD in China, the psychosocial adaptation of IBD patients and the associated factors were less explored.…”
Section: Introductionmentioning
confidence: 99%
“…When the child is young, this responsibility for diabetes management belongs solely to the parents, but as the child grows, the responsibility will gradually shift from the parent to the child. Hence, it is vital to consult and involve the parents, as their commitment and support are prerequisites for the well-being of the child [ 11 , 12 ]. Having to deal with illness management tasks in everyday life places a heavy burden on the children and their parents.…”
Section: Introductionmentioning
confidence: 99%